Town Law Books in East Central Europe - Šmídová Malárová, Lenka; Razim, Jakub (Lectures on East Central European Legal History, 2022)
This chapter focuses on the town law books written in the historical territory of Central and Eastern Europe. Town law books, in a broader sense, consist of a wide range of manuscripts. They are a result of cities’ literary production and include a considerable number of codes that served the municipal administration and jurisdiction. Using the example of the Czech lands, Slovakia, Hungary, Austria, and Poland, the authors seek to point out the role this crucial legal source plays, which mirrors the quality of legal culture and life in medieval and early modern cities. Our chapter contains several subchapters dedicated to each of the abovementioned countries. These subchapters begin with an explanation of the origins of towns in a particular region, followed by discussion about the municipal administration, the judiciary, and the nature of local municipal law and municipal documents. At the end of every subchapter, there is also a more detailed explanation of the selected legal source.KEYWORDS: town law books, municipal law, Magdeburg Law, municipal administration, Swabian Law, sources of municipal law, East Central Europe.